Modelling agaricoid fungi distribution in Andean forests of Patagonia - Romano, Gonzalo Matías (2017)
Agaricoid fungi of Subantartic forests have been vastly studied at a taxonomical and, to less extent, ecological level. These historical approaches have left large amounts of presence-only occurrences of several endemic species of the Andean region. Since sampling season in Patagonia is reduced to a minimum because of its large extension and climate conditions that govern the region,it is essential to focus on locations where subjects of study are present. Knowledge of patterns of fungal distributions can help lead future forest management investments as well as to guide efforts to delimit fungal hot-spots areas of conservation. The aim of the present work was to assess the potential distribution of a selection of 9 saprophytic and 9 ectomycorrhyzic gilled fungi based on their abundance, seasonality, occurrences in bibliography and etectability. Eighty localities were georreferenced for 260 occurrences of the species modelled. The ectomycorrhyzic Rhodophyllus patagonicus presents the most restricted distribution among all species studied while Psathyrella falklandica, saprophytic, has the most widespread distribution. Despite having different nutritional requirements, all species studied exhibit a very similar dependence with mean precipitation of the driest month and similar potential distributions. Distribution maps are provided for each species. Discussion on the dynamics and extent of fungal species distribution in Patagonia is also provided.